Phenotyping of hypertensive heart disease and hypertrophic cardiomyopathy using personalized 3D modeling and cardiac magnetic resonance imaging / Chuah Shoon Hui - Chuah, Shoon Hui (2020)
Differential diagnosis of hypertensive heart disease (HHD) and hypertrophic cardiomyopathy (HCM) is clinically challenging but important for treatment management. This study aims to phenotype HHD and HCM in 3D+time domain by using a multiparametric motion-corrected personalized modeling algorithm and cardiac magnetic resonance (CMR). 44 CMR data, including 12 healthy, 16 HHD and 16 HCM cases, were examined. Multiple CMR phenotype data consisting of geometric and dynamic variables were extracted globally and regionally from the models over a full cardiac cycle for comparison against the healthy models and clinical reports. Statistical classifications were used to identify the distinctive characteristics and disease subtypes with overlapping functional data, providing insights into the challenges for differential diagnosis of both types of disease. While HCM is characterized by localized extreme hypertrophy of the left ventricular (LV), wall thickening/contraction/strain was found to be normal and in synchrony, though it was occasionally exaggerated at normotrophic/less severely hypertrophic regions during systole to preserve the overall ejection fraction (EF) and systolic functionality. Additionally, we observed that hypertrophy in HHD could also be localized, although in less extreme conditions (i.e. more concentric). While fibrosis occurred mostly in those HCM cases with aortic obstruction, only minority of HHD patients were found to be affected by fibrosis. We demonstrated that subgroups of HHD (i.e. preserved and reduced EF: HHDpEF & HHDrEF) have different 3D+time CMR characteristics. While HHDpEF has cardiac functions in normal range, dilation and heart failure are indicated in HHDrEF as reflected by low LV wall thickening/contraction/strain and synchrony, as well as much reduced EF.